Mengukur Potensi Perpindahan Nasabah Perbankan Kategori Milenial pada Layanan Pembiayaan Fintech Lending - Muhammad Anif Afandi (Jurnal Ekonomi Indonesia, 2020)
The purpose of this study is to measure the potential of millennial banking customers to switch to the financing services of FinTech lending and its influencing factors in the area of DKI Jakarta. Multinomial Logistic Regression (MLR) method is applied as the dependent variable has more than two categories. The results showed that the likelihood for banking customers were reluctant, likely and willing to switch to the financing services of FinTech lending amounts to 7.73 percent, 97.19 percent and 2.81 percent, respectively. The most affecting factors of banking customers to switch to the FinTech lending are pricing problem and ease of use. Meanwhile, inertia serves as an inhibitory factor of customer switching. The results of this study provide useful information for the managerial level in the banking industries, FinTech lending as well as the regulators for determining the appropriate strategies and policies to cope with customer switching. Keywords: customer switching; banking; FinTech lending; MLR; DKI Jakarta ————————————————– Penelitian ini bertujuan untuk mengukur potensi perpindahan nasabah perbankan kategori milenial pada layanan pembiayaan FinTech lending di DKI Jakarta dan faktor-faktor yang memengaruhinya. Multinomial Logistic Regression (MLR) digunakan sebagai teknik analisis data karena variabel terikat terdiri dari lebih dari dua kategori. Hasil penelitian menunjukkan bahwa peluang nasabah perbankan yang tidak bersedia, mungkin pindah dan bersedia untuk pindah pada layanan pembiayaan FinTech lending masing-masing sebesar 7,73 persen, 97,19, persen dan 2,81 persen. Faktor yang paling memengaruhi terjadinya perpindahan nasabah tersebut adalah pricing problem dan ease of use. Selain itu, inertia menjadi faktor penghambat terjadinya perpindahan nasabah. Hasil penelitian ini memberikan informasi yang bermanfaat bagi pihak manajerial, baik pada industri perbankan, FinTech lending, maupun regulator untuk dapat menentukan strategi dan kebijakan yang tepat di tengah potensi terjadinya perpindahan nasabah.